A ray tracing method for radio wave propagation prediction on selected locations on Sun-U campus - Lim, Soo Yong * (Sunway University, 2012)
Radio propagation prediction is a crucial step to determine the propagation characteristics of any arbitrary installation for the implementation of a mobile radio system. In this paper, a ray tracing approach using image method is adopted to perform radio propagation predictions in two selected areas of Sun-U Campus, namely an empty hallway located on the second floor in the School of Computer Technology (SCT), and its adjacent academic staff rooms. The values of electrical parameter such as dielectric constant (relative permittivity) of different materials are altered assuming the walls that separate each academic staff room are made of rubber, glass, plasterboard, and concrete. How this variation affects radio wave propagation prediction is discussed while the main propagation mechanisms traveling along the empty hallway are reported. In addition, the reasons for an appropriate interval between two sampling points along a transmitter-receiver route are also illustrated and explained.